Penciptaan Evening Gown Inspirasi Bunga Tunjung Dengan Teknik Applique Dan Digital Printing - Ayunia, Khairunnisa; Suharno, Suharno; Marlianti, Mira (Jurnal Pendidikan dan Penciptaan Seni, 2025)
The fashion industry continues to grow with the demand for design innovation that combines cultural heritage and modern technology. This creation aims to present an evening gown inspired by the beauty and symbolism of the nymphaea flower through a combination of appliqué and digital printing techniques. The urgency of this research lies in the efforts to diversify sources of inspiration for fashion design, the use of technology to improve efficiency and visual detail, and the preservation of cultural values through contemporary interpretations. The novelty of this research lies in the integration of distinctive local floral inspiration with appliqué techniques enriched by digital printing details, which have not been widely explored in the context of evening gowns. This research method adapts the double diamond model, which includes the stages of discover, define, develop, and deliver. The results of this work are 3 evening gowns with nymphaea flower appliqué details enriched with texture and color through digital printing. This work was presented at Bandung Fashion Runway 2025 on TVRI West Java.